EPIDEMIOLOGY OF TUBERCULOSIS IN INDIA AND INTEGRATED APPROACH FOR NATIONAL LEVEL TUBERCULOSIS ELIMINATION STRATEGIES WITH A REVIEW ON THE CONTRIBUTION OF AYUSH SYSTEMS - Dr. Pranita S. Joshi Deshmukh; Dr. Sushil Deshmukh (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
The latest data on tuberculosis (TB) in India highlights significant trends in case reporting and treatment. In 2023, a substantial portion—approximately 33%—of the 25.5 lakh TB cases reported came from the private sector, marking a notable increase from just 1.9 lakh cases reported in 2015. Despite this growth, government health centres remain the primary source of notifications. There is slight rise to 27.8 lakh, up from 27.4 lakh the previous year, while the mortality rate remained steady at 3.2 lakh. It’s worth noting that India’s TB mortality decreased from 4.94 lakh in 2021 to 3.31 lakh in 2022, reflecting improvements in treatment and care. Crucially, India achieved its target for 2023 by initiating treatment for 95% of patients diagnosed with TB, underscoring the commitment to controlling and eventually eliminating the disease. The rise in multidrug-resistant tuberculosis (MDR-TB) is indeed a pressing concern, driven by several interrelated factors. Increased population density can lead to higher transmission rates, while global warming and pollution exacerbate health challenges, particularly in vulnerable communities. Poverty and illiteracy contribute significantly to the TB burden, as they often hinder access to healthcare, education about disease prevention, and adherence to treatment protocols. Discontinuity in treatment—whether due to lack of resources, patient awareness, or healthcare infrastructure—further complicates efforts to control TB and can lead to the development of drug resistance. Addressing these underlying issues is crucial for reducing the incidence of MDR-TB. This could involve implementing comprehensive public health strategies that focus on improving education, increasing access to healthcare, and ensuring consistent treatment. Enhanced community engagement and targeted interventions in high-risk populations will be vital in curbing the spread of MDR-TB and ultimately achieving TB elimination goals. Achieving the target of eliminating tuberculosis (TB) from India by 2025 will indeed require significant efforts across the entire healthcare system. Currently, Allopath government institutions and public health centres play a major role in this initiative. However, to enhance the effectiveness of TB elimination efforts, it’s essential to involve other organizations, particularly those in the AYUSH sector (Ayurveda, Yoga, Unani, Siddha, and Homeopathy). These institutions typically have the necessary infrastructure and manpower to support TB control initiatives. By implementing capacity-building programs, the government can equip these organizations to assist in early detection and treatment of TB cases. Additionally, incentivizing the reporting and management of TB cases in both private and public AYUSH institutions could lead to improved case identification and patient outcomes. Collaborative efforts, training, and resources directed toward these sectors could significantly bolster the overall strategy to combat TB, ultimately contributing to the goal of elimination by 2025. The review article explains the methodology to involve the existing system for early achievement of the elimination target. All systems of Healthcare in India should be involved for early achievement of elimination targets.